When genomic medicine reveals misattributed genetic relationships – the debate about disclosure revisited - Wright, C; Parker, M; Lucassen, A (Nature Publishing Group, 2018)
Purpose Accidental discovery of misattributed parentage is an age-old problem in clinical medicine, but the ability to detect it routinely has increased recently as a result of high-throughput DNA sequencing technologies coupled with family sequencing studies. Problems arise at the clinical-research boundary, where policies and consent forms guaranteeing nondisclosure may conflict with standard clinical care. Methods To examine the challenges of managing misattributed parentage within hybrid translational research studies, we use a case study of a developmentally delayed child with a candidate variant found through a large-scale trio genome sequencing study in which data from unrelated samples is routinely excluded. Results We discuss whether genetic parentage should be explicitly confirmed during clinical validation, thus giving greater weight to the diagnosis according to ACMG variant interpretation guidelines, and what tensions this approach would create. Conclusion We recommend that the possibility of finding and disclosing misattributed parentage should be addressed during the consent or pre-test counselling process, and that clinical relevance should determine whether or not to disclose results in the clinic. This proposition has implications for research governance, and implies that it may not always be possible to uphold nondisclosure commitments as investigations move from research to clinical care.